Analisis Pemikiran Al-Ghazali Tentang Etika Bisnis Islam dengan Relevansinya Transaksi Bisnis Pasar Modern di Mall Plaza Jember - Alwiatul Wardah; Muhammad Nizar; Muhammad Fahmul Iltiham (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In Islamic economics, business and ethics are not two conflicting concepts, but rather complementary. Business in Islam is not only a worldly affair but also part of the investment of the afterlife. Therefore, every business activity must be in accordance with moral and ethical principles based on Islamic values. Business ethics in Islam have a major influence on consumer trust and loyalty, as well as the sustainability of the business itself. Imam Al-Ghazali's thoughts on Islamic business ethics emphasize the importance of the principles of justice, honesty, and trust in economic transactions. This study aims to analyze Al-Ghazali's thoughts on Islamic business ethics and their relevance in business transactions in the modern market, especially in Plaza Jember. In the context of modern business, the ethical principles taught by Al-Ghazali are still very relevant, including the prohibition of usury, the distribution of wealth through zakat, and transparency in trade. Although his thoughts originated in the 11th century, the concepts he put forward can still be adapted in the contemporary economic system. The results of this study indicate that Islamic business ethics play an important role in building a fair and sustainable trading system. In modern markets such as Plaza Jember, the application of Islamic business ethics can increase customer trust and create a healthy business environment. By understanding and implementing the concept of Islamic business ethics, business actors can achieve profits not only in the world but also in the hereafter.